Effects of angle formation between melted zone and friction direction on thermal fatigue and wear resistance of truck drum brake. (April 2021) - Yu, Dahui; Zhou, Ti; Zhou, Hong; Xu, Yao; Zhang, Peng; Yan, Yuying
The failure of grey cast iron drum brake is mainly caused by thermal fatigue crack running through the top along the axial direction, which has the characteristics of regional failure. By using the advantages of laser fabrication technology, the single models with five different angles combined with the anti-crack ring were designed. The optical microscope, scanning electron microscope and X-ray diffraction were used to characterize the microstructure and phase of the drum brake material grey cast iron and the bionic coupling unit. Both single models and double combination models were tested for thermal fatigue and wear after thermal fatigue, respectively. The effects of angle on the thermal fatigue and wear resistance of the bionic coupling models were investigated. Experimental results show that the microstructure of the unit was better than that of the base grey cast iron due to the appearance of ledeburite, martensite and residual austenite after laser treatment. Besides, thermal fatigue crack has a great influence on wear performance. The thermal fatigue crack and wear loss weight are the least in the model with anti-crack ring + 45°angle, the main crack length is the shortest. The service life of the drum brake with the double combination bionic coupling model is increased by 50% compared with that of the untreated drum brake in bench test.